Zmiany w nadzorze i regulacji sektora ubezpieczeniowego w Unii Europejskiej - CEIOPS a procedura Lamfalussy'ego - Kurek, Robert (Changes in the Supervision and Regulation of the Insurance Sector in the European Union - Ceiops vs. Lamfalussy's Procedure, 2006)
In the article the author presents the new system of making law in the financial sector of the European Union - the so called Lamfalussy's procedure, taking into consideration the levels of making that law in the insurance and pension funds sectors. Simultaneously he presents the place of the new institution dealing with the supervision on the insurance and pension funds market (CEIOPS) in the context of Lamfalussy's procedure. Moreover the organizational structure of CEIOPS and its tasks have been characterized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 250-259